Data Mining Penjualan Produk Dengan Metode Apriori Pada Indomaret Galang Kota - Sheih Al Syahdan; Anita Sindar (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2018)
The large number of transactions, companies need analytical tools to provide information that is useful for the company in determining the layout of goods, what items are most in demand by consumers and others. As experienced by several other supermarkets, product placement is a major problem. Data mining is a technique for digging up information that is hidden or hidden. This study will identify several types of association rules relating to sales transaction data, namely support and confidence values. The data used are 25 food and beverage products. Data mining technique uses associative rule with the Apriori method, aims to find a combination of items with a frequency pattern of the transaction results. After all high frequency patterns are found, then the association rules that meet the minimum requirements are found for confidence associative rules A → B minimum confidence = 25%, confidence value of A → B rules.